Pathways to the Professoriate: The Experiences of First-Generation Latino Undergraduate Students at Hispanic Serving Institutions Applying to Doctoral Programs - Andrew Martinez (MDPI AG, 2018)
Despite representing the largest ethnic minority group in the United States, Latinos remain underrepresented in the professoriate. Although Latinos are increasingly attending college, fewer graduate and even fewer continue to pursue graduate school. Prior research has explained the challenges that first-generation college students encounter in post-secondary contexts. Given that Latino college students are likely to be first-generation, understanding the experiences of first-generation Latino undergraduate students who aspire to be professors and are applying to graduate school can help illuminate what factors help support this underrepresented group in pursuing a career in the academy. Using qualitative approaches, this study describes the experiences of 15 first-generation undergraduate Latino students in a grant funded academic program that provides them with a plethora of resources to help prepare them for graduate school applications. The findings suggest how early exposure to information about applying to graduate school, access to role models, familial support and understanding of an academic career and having a community of peers with similar ambitions can help cultivate an environment where first-generation, Latino students remain inspired and committed to pursuing graduate school in efforts to become a professor.